Transcriptional and Epigenetic Factors Associated with Early Thrombosis of Femoral Artery Involved in Arteriovenous Fistula - Vikrant Rai; Devendra K. Agrawal (Proteomes, 2022)
Arteriovenous fistulas (AVFs), created for hemodialysis in end-stage renal disease patients, mature through the outward remodeling of the outflow vein. However, early thrombosis and chronic inflammation are detrimental to the process of AVF maturation and precipitate AVF maturation failure. For the successful remodeling of the outflow vein, blood flow through the fistula is essential, but early arterial thrombosis attenuates this blood flow, and the vessels become thrombosed and stenosed, leading to AVF failure. The altered expression of various proteins involved in maintaining vessel patency or thrombosis is regulated by genes of which the expression is regulated by transcription factors and microRNAs. In this study, using thrombosed and stenosed arteries following AVF creation, we delineated transcription factors and microRNAs associated with differentially expressed genes in bulk RNA sequencing data using upstream and causal network analysis. We observed changes in many transcription factors and microRNAs that are involved in angiogenesis; vascular smooth muscle cell proliferation, migration, and phenotypic changes; endothelial cell function; hypoxia; oxidative stress; vessel remodeling; immune responses; and inflammation. These factors and microRNAs play a critical role in the underlying molecular mechanisms in AVF maturation. We also observed epigenetic factors involved in gene regulation associated with these molecular mechanisms. The results of this study indicate the importance of investigating the transcriptional and epigenetic regulation of AVF maturation and maturation failure and targeting factors precipitating early thrombosis and stenosis.